DIGITAL GAMES AND HETERONORMATIVITY: THE CASE OF CHINA’S ‘LOSERS’ - Szablewicz, Marcella (AoIR Selected Papers of Internet Research, 2015)
In light of the ongoing controversy surrounding Gamergate and the hostility directed against feminist critiques of digital games in the United States, this paper takes as its subject the nature of sexuality and heteronormativity within Chinese online gaming culture. Within China, as with other parts of the world, online games and gamer lifestyles are often the subject of /platform for crude sexual slang. For example, playing online games is considered to be one of the main preoccupations of the male ‘diaosi’ or ‘loser,’ a young person known for his lack of sexual prowess. Games such as League of Legends are given nicknames such as ‘lu a lu,' alluding to the act of masturbation, and male gamers who form intimate bonds of friendship are described as ‘gaoji,' or ‘acting gay.’ Has this terminology led to a hostile environment for female and non-heteronormative gamers, or, do these humorous and crude phrases serve as a point of critique and acceptance? In the context of the Chinese Internet, it has long been noted that many of the most popular vulgar terms also serve a political purpose. Consider the widespread use of ‘cao ni ma’ (grass mud horse), which, aside from being a homophone for a curse word, has also become a symbol of Internet activism and rebellion. Do the aforementioned slang terms function in the same way? In considering these questions, this paper will engage with both Western and Chinese scholarship on gender and sexuality in online gaming culture.